2021
DOI: 10.3389/fgene.2021.741243
|View full text |Cite
|
Sign up to set email alerts
|

SMRT Sequencing of the Full-Length Transcriptome of the Coelomactra antiquata

Abstract: Coelomactra antiquata is an important aquatic economic shellfish with high medicinal value. However, because C. antiquata has no reference genome, a lot of molecular biology research cannot be carried out, so the analysis of its transcripts is an important step to study the regulatory genes of various substances in C. antiquata. In the present study, we conducted the first full-length transcriptome analysis of C. antiquata by using PacBio single-molecule real-time (SMRT) sequencing technology. The results iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…We further analyzed the structure of the transcripts using various pieces of biological software. The animalTFDB 3.0 software predicted 1906 TFs and most of the TFs belonged to the bHLH and zf-C2H2 families, similar to a study on another shellfish, Coelomactra antiquata [ 35 ]. The MISA 1.0 software predicted 8873 SSRs, which was much more than the 2151 and 4279 SSRs reported by the second-generation RNA-seq [ 33 , 36 ].…”
Section: Discussionsupporting
confidence: 63%
“…We further analyzed the structure of the transcripts using various pieces of biological software. The animalTFDB 3.0 software predicted 1906 TFs and most of the TFs belonged to the bHLH and zf-C2H2 families, similar to a study on another shellfish, Coelomactra antiquata [ 35 ]. The MISA 1.0 software predicted 8873 SSRs, which was much more than the 2151 and 4279 SSRs reported by the second-generation RNA-seq [ 33 , 36 ].…”
Section: Discussionsupporting
confidence: 63%
“…SMRT sequencing has the characteristics of high accuracy, reliability, long reading, and sequencing speed, and it enables animal genomic research without a reference genome ( Hestand & Ameur, 2019 ; Jayakumar & Sakakibara, 2019 ; Zhang et al, 2019 ; Xiao & Zhou, 2020 ; Deng et al, 2021 ). Since the C. chinensis is an economically important snail with high medicinal value, and it has vital scientific research potential ( Zhou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…By data analysis, 26,312 unigenes with a mean length of 2,572 bp were obtained in the study. Deng et al used the same technology to sequence the no-reference-genome species Coelomactra antiquata and found a total of 39,209 unigenes with an average length of 2,732 bp ( Deng et al, 2021 ). Similarly, Yang et al found 63,801 full-length transcripts in the three developmental stages of Rhynchophorus ferrugineus , with an average length of 2,964 bp ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, third-generation sequencing (e.g., single-molecule real-time [SMRT]) technologies have been able to address the shortcoming of NGS. Single-molecule real-time sequencing can obtain full-length transcript sequences, without assembly, providing a better opportunity to explore whole-transcriptome profiling in non-model species [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%